Novel reciprocal interaction of lncRNA HOTAIR and miR‐214‐3p contribute to the solamargine‐inhibited PDPK1 gene expression in human lung cancer - Tang, Qing (J Cell Mol Med, 2019)
Solamargine (SM) has been shown to have anti‐cancer properties. However, the underlying mechanism involved remains undetermined. We showed that SM inhibited the growth of non‐small cell lung cancer (NSCLC) cells, which was enhanced in cells with silencing of long non‐coding RNA (lncRNA) HOX transcript antisense RNA (HOTAIR), while it overcame by overexpression of HOTAIR. In addition, SM increased the expression of miR‐214‐3p and inhibited 3‐phosphoinositide‐dependent protein kinase‐1 (PDPK1) gene expression, which was strengthened by miR‐214‐3p mimics. Intriguingly, HOTAIR could directly bind to miR‐214‐3p and sequestered miR‐214‐3p from the target gene PDPK1. Intriguingly, overexpression of PDPK1 overcame the effects of SM on miR‐214‐3p expressions and neutralized the SM‐inhibited cell growth. Similar results were observed in vivo. In summary, our results showed that SM‐inhibited NSCLC cell growth through the reciprocal interaction between HOTAIR and miR‐214‐3p, which ultimately suppressed PDPK1 gene expression. HOTAIR effectively acted as a competing endogenous RNA (ceRNA) to stimulate the expression of target gene PDPK1. These complex interactions and feedback mechanisms contribute to the overall effect of SM. This unveils a novel molecular mechanism underlying the anti‐cancer effect of SM in human lung cancer.